PENGENDALIAN PEMANFAATAN RUANG PADA KAWASAN PARIWISATA BERORIENTASI PADA KEADILAN DAN KESEJAHTERAAN MASYARAKAT - Sudira, I Made (Jurnal Aktual Justice, 2021)
The rapid development of tourism in Indonesia, particularly in Bali, is serious challenges in controlling and utilizing spaces. The establishment of local protected areas (sacred areas, borders, green open spaces), as part of protected areas through the Regional Regulation of Bali Province Number 16 of 2009, which was amended by the Regulation of Bali Province Number 3 of 2020 concerning the Bali Provincial Spatial Plan, is considered unfair by a group people because it delimits the utilization of property rights to land in the area. As a result, numerous violations occur in spatial regulations in tourism areas, especially in the areas designated as protected areas. This study aims to find, discover and formulate a model for controlling the spatial utilization in tourism area that is oriented towards justice and welfare of the community. The research method used in this study is normative legal research method supported with statute approach and conceptual approach. The research materials used included primary legal materials and secondary legal material collected through note-taking technique. And than the analysis of the legal materials was carried out qualitatively assisted with reasoning and legal argumentation techniques and the results are then presented descriptively. Based on the presentation of the results of the research and the discussion, it can be concluded that the ideal model of the spatial utilization and control comprises the model that is based on the concept of bioregionalism, that is to say, the concept of developing and fulfilling the living needs through adjusting the ecosystem of local communities by preserving and fostering the ecosystem to support the life of the economy. This model is a combined concept in controlling the use of space, namely by not destroying the environment and its ecosystem and on the other hand, the community is not economically disadvantaged in meeting their needs in order to achieve prosperity. This model is also in accordance with the provisions of Article 2 letter h of Law Number 32 of 2009, which stipulates that the environmental protection and management is carried out based on the principle of ecoregion, in that, the environmental protection and management shall consider the characteristics of the natural resources, ecosystems, geographical conditions, the culture of the local community, and the local wisdom.